Teacher’s Voice in Online Task-Based Language Teaching on EFL Writing Context - Hasanah, Uswatun; Sahril Nur; Wattiheluw , Nurlaila (LETS: Journal of Linguistics and English Teaching Studies, 2023)
In light of the pandemic, online learning has become increasingly popular. Thus, students' interest and engagement are two of the primary concerns of teachers regarding online teaching. online Task-Based Language Learning (TBLT) is one of them. Based on the issue, this research conducted to explore teachers' voices in online TBLT of EFL writing contexts. The researchers employed a descriptive-qualitative approach. The interview was used to collect data from two EFL teachers at IAIN Bone and IAIN Ambon. The data obtained from interview process then analyzed descriptively. According to the findings of the study, the teachers believe that implementing online TBLT in EFL writing context has numerous advantages. However, the teachers also face several challenges in implementation. The teachers expressed the hope that online TBLT would be a good choice as one of the current strategies for teaching EFL writing. The study could have implications for online English teaching and learning in terms of pedagogy both theoretically and practically, aiding teachers and students in adopting TBLT